A First Step to Novel Approach for Treating Alkali Injury of the Cornea: Effect of Platelet Rich Fibrin Lysates on Cultured Rabbit (Oryctolagus cuniculus) Limbal Stem Cell Proliferation Exposed by Sodium Hydroxide - Prabawati, Wahyu Endah; Suhendro, Gatut; Retnowati, Endang (Folia Medica Indonesiana, 2022)
Highlights: • Sodium hydroxide causing platelet rich fibrin stimulates limbal stem cell proliferation in chemical trauma. • Limbal stem cell niche and influences limbal stemness was repaired by Platelet Rich Fibrin. Abstract: Chemical injuries of the eye produce extensive damage to the ocular surface and limbal stem cells, resulting in permanent unilateral or bilateral visual impairment. Alkali injuries occur more frequently than acid injuries. Platelets are a rich source of potential wound healing, promoting polypeptide growth factors. This study aimed to investigate the effect of platelet-rich fibrin (PRF) lysates on limbal stem cell proliferation, which was exposed to sodium hydroxide that resembled limbal stem cell deficiency due to chemical trauma. Confluent rabbit (Oryctolagus cuniculus) limbal stem cells wounded using 20µL of 0.00625 M sodium hydroxide (pH 13) were treated with platelet-rich fibrin lysates (PRF) (0, 5, and 10%). PRF lysates were prepared from peripheral rabbit blood according to Choukroun's method without using anticoagulant and foreign factors for platelet activation. The proliferation of limbal stem cells was measured by a 3-(4,5-dimethylthiazol-2-yl)-2.50 diphenyl tetrazolium bromide (MTT) colorimetric assay at 24, 48, and 72 hours after exposure to sodium hydroxide. Proliferation significantly increased limbal stem cells with PRF lysates 5% (p<0.01) and 10% (p<0.01) group compared with the control (PRF 0%). There was no significant difference between PRF lysates of 5% and 10% (p>0.01). The highest proliferation of limbal stem cells was found in the PRF lysates 5% group after 48 hours (100.24%). PRF stimulated limbal stem cell proliferation in chemical trauma caused by the sodium hydroxide model. PRF repaired the limbal stem cell niche and influenced the limbal stemness. The present findings warrant further research on PRF as a novel alternative treatment for limbal stem cell deficiency.